How Islamic Rural Bank Overcomes the Trade-off Between Sustainability and Outreach: Does Market Competition Matter? - Muhari, Syafaat; Jumani, Zulfiqar Ali (Muhammadiyah University Press, 2024)
There was no consensus how to deal the trade-off between maintaining sustainability and outreach of microfinance institutions among researchers. The paper provides time series data which includes monthly industry data from Islamic Rural Bank for a period of more than 14 years starting from January 2009 to March 2023. In the first analysis, an estimate of the level of market competition is compute by the Lerner Index (LI) of each period. Furthermore, the efficiency analysis of Data Envelopment Analysis (DEA) is used to measure efficiency which allows estimation of efficiency performance using multiple inputs and outputs to understand how Islamic Rural Bank deal with sustainability and outreach. In the end, a Vector Autoregression/Vector Error Correction Model (VAR/VECM) analysis is used to analyse the relationship between the level of market competition and the efficiency of Islamic Rural Bank in achieving sustainability and outreach objectives. The results of the study suggest that by using a production approach Islamic Rural Bank is able to operate efficiently while maintaining the sustainability and outreach objectives without trade-offs. In addition, market competition has a moderate influence on achieving sustainability goals and their outreach. This research examines how Islamic Rural Bank as one of the microfinances to overcome the trade-off between the goals among high competition and the increasing of financial needs by customers. The Microfinance model from Islamic Rural Banks can be replicated to other microfinance institutions (MFIs) to reach both outreach and sustainability goals.